Analysis of laboratory adhesion studies in eroded enamel and dentin: a scoping review - Madalena Belmar da Costa; António H. S. Delgado; Teresa Pinheiro de Melo; Tomás Amorim; Ana Mano Azul (Medical Journals Sweden, 2021)
Aim To summarize and report laboratory studies of adhesion in eroded substrates, which used bond strength as an outcome measure. To determine the strategies available to overcome bonding difficulties, the quality and consistency of the methodology and to find evidence gaps. Materials and Methods The present review followed PRISMA-ScR guidelines. A search was conducted on PubMed/Medline, Scopus and EMBASE (Ovid) databases to identify published peer-reviewed papers (2010-2020). For final qualitative synthesis, 29 articles were selected which respected the inclusion criteria. Data charting was carried out, independently, by two reviewers and quality assessment of the articles was performed. Results The primary studies included fall into four major categories: comparison of restorative materials and application modes, enzymatic inhibitors, surface pretreatments or remineralization strategies. Most studies found evaluated dentin (76%), while 17% evaluated enamel, and 7% evaluated both substrates. The majority of the studies reported an effective intervention (83%). Bond strength to eroded dentin is significantly reduced, while in enamel erosion is beneficial. The bond strength to eroded dentin is material-dependent and favored in systems containing 10-MDP. Great disparities among the erosion models used were found, with citric acid in different concentrations being the preferred method, although standardization is lacking. Conclusions Adhesives containing 10-MDP show beneficial results in eroded dentin, and surface preparation methods should be considered. Studies which evaluated adhesion to eroded enamel/dentin show high heterogeneity in what concerns aims and methodology. Strategies that focus on remineralizing dentin and strategies to protect bond longevity in this substrate require further research.